EVALUATION OF LANDSCAPE ELEMENT FOR PEOPLE WITH DISABILITIES AT SAMARENDAH PARK IN SAMARINDA - Levarinda, Kathy Kezia; Jordan, Nadia Almira (Border: Jurnal Arsitektur, 2021)
City parks as public urban infrastructure are required to provide facilities that can accommodate all levels of society, including people with disabilities as park users. One of the public green open spaces in Samarinda City, namely Samarendah Park, is known to still lack attention to accessible support facilities for people with disabilities. This research aims to evaluate the suitability of landscape element conditions in Samarendah Park for people with disabilities to the accessibility standards of city parks. The research approach method used is qualitative in the form of mapping analysis of landscape elements and supporting facilities of Samarendah Park which will then be evaluated with policy documents and related theories to be further calculated using a percentage formula that displays a large percentage of conformity conditions. The results of the analysis showed that the availability of landscape elements and supporting facilities in Samarenda Park was adequate because the laying was evenly distributed throughout the park area, but from the results of conformity evaluation, it was obtained that availability alone was not enough to support the activities of visitors because functionally and condition there are still landscape elements and supporting facilities that are not even in accordance with accessibility standards followed by large percentages produced.